Incremental benefits of EEG informed fMRI in the study of disorders related to meso-corticolimbic dopamine pathway dysfunction: a systematic review of recent literature - Syed Nasser, Nisha; Ibrahim, Buhari; Sharifat, Hamed; Abdul Rashid, Aida; Suppiah, Subapriya (Churchill Livingstone, 2019)
Functional magnetic resonance imaging (fMRI) is a non-invasive imaging modality that enables theassessment of neural connectivity and oxygen utility of the brain using blood oxygen level dependent(BOLD) imaging sequence. Electroencephalography (EEG), on the other hands, looks at cortical electricalimpulses of the brain thus detecting brainwave patterns during rest and thought processing. The combi-nation of these two modalities is called fMRI with simultaneous EEG (fMRI-EEG), which has emerged as anew tool for experimental neuroscience assessments and has been applied clinically in many settings,most commonly in epilepsy cases. Recent advances in imaging has led to fMRI-EEG being utilized in beha-vioural studies which can help in giving an objective assessment of ambiguous cases and help in theassessment of response to treatment by providing a non-invasive biomarker of the disease processes.We aim to review the role and interpretation of fMRI-EEG in studies pertaining to psychiatric disordersand behavioral abnormalities.